An archaeology of unchecked capitalism : from the American rustbelt to the developing world - Shackel, Paul A. (Berghahn Books, 2020)
"The racialization of immigrant labor and the labor strife in the coal and textile communities in northeastern Pennsylvania appears to be an isolated incident in history. Rather this history can serve as a touchstone, connecting the history of the exploited laborers to today's labor in the global economy. By drawing parallels between the past and present - for example, the coal mines of the nineteenth-century northeastern Pennsylvania and the sweatshops of the twenty-first century in Bangladesh - we can have difficult conversations about the past and advance our commitment to address social justice issues"--